Life History Traits and Population Growth of Greenhouse Whitefly (Trialeurodes vaporariorum Westwood) on Different Tomato Genotypes - Prijović, Mirjana R; Marčić, Dejan; Drobnjaković, Tanja M; Međo, Irena S; Perić, Pantelija (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
The effects of five tomato genotypes (cv. Narvik and hybrids NS-6, Tamaris, Alliance and Marko) on the survival, reproduction, development and population growth of the greenhouse whitefly Trialeurodes vaporariorum were examined. A laboratory population of T. vaporariorum had been reared on tobacco plants for three years before the study. Females that laid eggs on the genotype Marko lived significantly longer and their offspring needed significantly shorter periods to develop than females on the genotype Narvik. The highest gross and net fecundity rates were found in females on the genotype Marko (36.74 eggs/female and 27.93 eggs/female, respectively) and they differed significantly from the corresponding rates of females living on the genotype NS-6 (18.55 eggs/female and 15.33 eggs/female), who had the lowest fecundity rates. The highest gross and net fertility rates were also found in females on the genotype Marko (31.24 adults/female and 23.73 adults/female), and they were significantly higher than those of females living on NS-6 (14.85 adults/female and 12.53 adults/female). Besides, net fertility rate of the females living on the genotype Narvik (13.80 adults/female) was also significantly lower than the rate of females on Marko. The instantaneous rates of increase showed no significant difference over a 10-day interval following the start of oviposition, while the increase rate was significantly higher on the genotype Marko after 12, 14 and 16 days, compared to the genotype NS-6. Eighteen, 20 and 22 days after the beginning of oviposition, the instantaneous rate of increase on the genotype Marko was significantly higher than it was on NS-6 and Narvik. Our data provide a basis for further research aiming to improve programs of integrated management of greenhouse whitefly.